Mask - Hannigan, Kate (Hannigan, Kate. League of Secret Heroes, 2020)
Akiko, Mae, and Josie, also called the Infinity Trinity, spring into action after learning that a spy is betraying secrets to the Japanese military--and that Akiko's mother may be involved.